Formation of gender identities in Republican Turkey and women's narratives as transmitters of 'herstory' of modernization - (:unkn) unknown (CARNEGIE MELLON UNIV PRESS, 2001)
The article tries to uncover women's narratives as transmitters of 'herstory' of modernization in Turkey after the foundation of Turkish Republic in 1923. Based on personal narratives collected through a research project carried out by the Women's Library, Istanbul, the authors suggest historical processes of modem Turkish femininity and point to the gendered nature of the public rhetoric and discourses, social mores and conduct, as well as daily practices both in the public and the private sphere, generated by the modernization project. These discourses defined the 'new women' as 'modern but virtuous' and set the limits to what degree the women could be 'modernized' while 'traditional womanhood' was scrutinized. The tensions that these women lived through between tradition and modernity are best revealed in the oral history interviews with women who are almost at the age of the Republic. The first-person narratives also provide an interesting account of women's adaptive strategies in dealing with such tensions.